Resilience - Gucciardi, Daniel (SAGE Publishing, Inc, 2014)
Most athletes will encounter one or more major setbacks or adversities during their sporting career. An elite athlete may, for example, experience a career-threatening injury, garner demotion from a top-tier team because of poor performance, or need to relocate to another country to continue competing in their sport. Despite the potential for setbacks and adversities to negatively influence one's developmental trajectories, in some cases, and for some athletes, exposure to major assaults on one's typical level of functioning or performance does not always result in negative outcomes. Why is it that some athletes bounce back from adversity or experience minimal disruption when faced with these major assaults? The concept of resilience is central to coping with such demands and challenges. Although there remains considerable debate regarding a formal definition, common themes among most contemporary conceptualizations reveal that resilience encapsulates one's capacity to regain or sustain relatively stable, healthy levels.